Influence of Citric Acid on the Vitality of Stem Cells from Apical Papilla - Hristov Kr. (Sciendo, 2018)
The endodontic treatment of immature permanent teeth with necrotic pulp is a serious clinical challenge. The chemical agents, used in regenerative procedures, should be selected not only based on their bactericidal/bacteriostatic properties, but also on their ability to ensure the survival of the patient’s stem cells. The aim of this study was to evaluate the effect of citric acid on the vitality of SCAP in a model of an immature tooth root. Models of immature roots were created from 12 freshly extracted teeth. The models were gas sterilized with ethylene oxide and they were separated into three groups, based on the used combinations of irrigants: 1) 1.5% sodium hypochlorite / 17% EDTA; 2) 1.5% sodium hypochlorite / 10% citric acid; 3) saline. SCAPs in a hyaluronic acid–based scaffold were seeded into the canals and cultured for 7 days. Viable cells were quantified using a colorimetric assay. There was no statistically significant difference between the groups, irrigated with NaOCl/EDTA and NaOCl/citric acid. The results from our experiment show that 10% citric acid can be used in combination with 1.5% NaOCl in a regenerative endodontic procedure.